ReconOS: An Operating System Approach for Reconfigurable Computing - Agne, Andreas; Happe, Markus; Keller, Ariane; Lubbers, Enno; Plattner, Bernhard; Platzner, Marco; Plessl, Christian (IEEE MICRO, 2014)
The ReconOS operating system for reconfigurable computing offers a unified multithreaded programming model and OS services for threads executing in software and threads mapped to reconfigurable hardware. The OS interface lets hardware threads interact with software threads using well-known mechanisms such as semaphores, mutexes, condition variables, and message queues. By semantically integrating hardware accelerators into a standard OS environment, ReconOS allows for rapid design-space exploration, supports a structured application development process, and improves the portability of applications between different reconfigurable computing systems.